THE INFLUENCE OF INFORMATION TECHNOLOGY USE ON DIGITAL PAYMENT USE WITH SOCIAL MEDIA COMMUNITY AS A MODERATING VARIABLE - Maria Natalia Damayanti Maer (Petra Christian University, 2026)
This study examines the influence of information technology use on digital payment use, with social media communities as a moderating variable. A quantitative approach was used with primary data collected from 202 Surabaya residents who had used mobile payments for shopping and participated in social media communities. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that information technology use has a positive relationship with digital payment use, although the effect is significant only at the 10% level. Social media communities have a stronger positive relationship with digital payment use. The interaction between information technology use and social media communities is also positive and significant at the 10% level, providing cautious support for the moderating effect. These findings suggest that the use of digital devices, internet access, service applications, and transaction information can support digital payment use, particularly when users also obtain information, recommendations, and assistance through social media communities. For businesses and service providers, technology development should therefore be supported by credible communication and community engagement. The study contributes to the discussion of digital payment use by showing that technological use and the social environment may work together in shaping user behavior.